Artificial Intelligence for the Internet of Everything - Lawless, William, editor 648641; Mittu, Ranjeev, editor 648642; Sofge, Donald , editor 648643; Moskowitz, Ira S., editor 648644; Russell, Stephen; ScienceDirect (Online service) 7722 (London : Academic Press, an imprint of Elsevie,r, 2019)
Artificial Intelligence for the Internet of Everything considers the foundations, metrics and applications of IoE systems. It covers whether devices and IoE systems should speak only to each other, to humans or to both. Further, the book explores how IoE systems affect targeted audiences (researchers, machines, robots, users) and society, as well as future ecosystems. It examines the meaning, value and effect that IoT has had and may have on ordinary life, in business, on the battlefield, and with the rise of intelligent and autonomous systems. Based on an artificial intelligence (AI) perspective, this book addresses how IoE affects sensing, perception, cognition and behavior.